PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP KEPUASAN KONSUMEN (Studi kasus pada Konsumen Rumah Makan Ayam Nelongso Malang) - Sri Utami; Muhammad Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACKThe purposes of this study are to find out and analyze of three independent variable Customer Relationship Management (CRM)  : (1) Commitment, (2) Communication, (3) Quality of Service on through Customer Satisfaction. This study used descriptive quantitative research. The population of this study are the customers of restaurant Ayam Nelongso Malang by the sampling of female customers who had purchased and customers who had loyal customers eat food. The accidental sampling used convenience sampling with the amount of respondent are 92. This study used multiple linear regression analysis. The result of this study are as follows : Commitment has an effect and significantly influence on the Customer Satisfaction  with  3,700 and significant value is 0,00 (2) Communication has an effect and significantly on the Customer Satisfaction with  4,798 and significant value is 0,00 (3) Quality of service has an effect and significantly influence on the Customer Satisfaction with  and significant value is 0,00 (4) Commitmen, Communication, Quality of service and significantly influence on the Customer Satisfaction  33,249 and significant value is 0,00. Keywords : Customer Relationship Management (CRM), Commitment, Communication, Quality of Service To Customer Satisfaction